Diverse Continental Subduction Scenarios Along the Arabia‐Eurasia Collision Zone. Issue 14 (21st July 2018) - Kaban, Mikhail K.; Petrunin, Alexey G.; El Khrepy, Sami; Al‐Arifi, Nassir
Abstract: It is generally accepted that convergence of the Arabian and African plates is a subduction‐dominated process. However, the subduction scenarios are still debatable. Here we present a 3‐D model of the mantle to a depth of 700 km, based on a joint interpretation of the seismic tomography, residual topography, residual mantle gravity field, and seismicity. At the northwestern edge of the collision zone, we only observe partial underthrust of the Eurasian plate under the West Greater Caucasus. We suggest that this is the initial stage of subduction polarity reversal after the break off of the plate formerly subducted northward. To the southeast, counteracting subduction zones are found beneath northwest Zagros in the south and beneath the East Greater Caucasus and Alborz in the north. This scenario is likely the result of highly buoyant and weak blocks of the Lesser Caucasus, Alborz, and northwest Zagros, which are underlain in the south by the Arabian plate and the Scythian plate and South Caspian from the opposite side. Further to the southeast, a delaminated lithospheric slab is observed under southeast Zagros, while the Arabian and Eurasian plates only partially underthrust East Zagros and Kopet Dagh, respectively. In the southern part of the collision zone under Makran, only remnants of the formerly subducted slabs are found below 200 km. Plain Language Summary: Continental collision zones are a result of plate tectonics on the planet Earth, when moving lithospheric plates collide at convergent boundaries. This process causes enormous concentration of deformations and stresses leading to increased seismic activity and large earthquakes, which can destroy entire cities. On the other hand, the collision process may also lead to formation of large sedimentary basins bearing ore and hydrocarbon deposits. Therefore, understanding of the mechanisms governing this process is crucial for human habitat. It is generally accepted that convergence of the Arabian and Eurasian plates is a subduction‐dominated process, when one plate penetrates under another along an inclined subduction zone. However, the subduction scenarios are still debatable. Here, we present a 3‐D model of the mantle to a depth of 700 km, based on a joint interpretation of various geophysical data. For the first time, we demonstrate an image of the counter‐acting subduction zones beneath Zagros in the South and beneath the East Greater Caucasus and Alborz in the North. This observation contradicts the conventional view of the northward subduction at the northern flank of the Arabia‐Eurasia plate boundary. These results have important implications for the debates concerning evolution and dynamics of continental collision zones. Key Points: We found principal changes of the subduction scenarios in different parts of the Arabia‐Eurasia collision zone In the Western Great Caucasus we propose initiation of subduction polarity reversal Counteracting subduction zones are located beneath northwest Zagros in the south and beneath the East Greater Caucasus and Alborz in the north